Research on Dance Teaching Mode Based on Flipped Classroom in the Internet +Age (Informatica, 2019)
The development of Internet technology has injected new impetus into the reform of education, and also posed new challenges to the traditional teaching mode. In recent years, as an extension of educational informationization, the flipped classroom has developed rapidly, and academic attention has increased year by year. At present, the flipped classroom in Colleges and universities in China has penetrated into many disciplines. Dance teaching should conform to the development of the times, optimize the teaching mode of dance education, open up innovative consciousness, and form a multi-channel teaching pattern. On the basis of discussing the theoretical and practical research on the mode of flipping classroom teaching in the dance teaching, this paper puts forward and designs the structure map of the pattern of the teaching mode of the flipped class in the ordinary university, and carries out a 4 month teaching experiment for the dance students. Through the analysis and verification of the data from the investigation and feedback, the conclusion is that the teaching mode of the dance flipping classroom has significant effect on improving the students’ basic dance quality, dance performance and autonomous learning ability